Atomically resolved real-space imaging of hot electron dynamics - Lock, D. (Nat Commun, 2015)
The dynamics of hot electrons are central to understanding the properties of many electronic devices. But their ultra-short lifetime, typically 100 fs or less, and correspondingly short transport length-scale in the nanometre range constrain real-space investigations. Here we report variable temperature and voltage measurements of the nonlocal manipulation of adsorbed molecules on the Si(111)-7 × 7 surface in the scanning tunnelling microscope. The range of the nonlocal effect increases with temperature and, at constant temperature, is invariant over a wide range of electron energies. The measurements probe, in real space, the underlying hot electron dynamics on the 10 nm scale and are well described by a two-dimensional diffusive model with a single decay channel, consistent with 2-photon photo-emission (2PPE) measurements of the real time dynamics.